University library practices in Metro Manila in relation to ownership versus access issue of serial publications - Balagot, Arlene A.; Cabbab, Johann Frederick A. (Quezon City : Institute of Library Science, University of the Philippines Diliman, 2001)
This paper sought to investigate the serials collection development situation of academic libraries in Metro Manila in line with the issue of ownership versus access. It also determined how widespread electronic serials are among these libraries. Lastly, this study investigated how these libraries adopt to electronic serials as a new format for providing information. The underlying basis for this study is cost effectiveness, ease of use and availability of materials.
This study investigated the problem by using descriptive survey method. In general, it aimed to find out the present state of collection development of academic libraries within Metro Manila, in connection with ownership versus access.
The study was participated by four (4) universities in Metro Manila that incorporate both ownership and access model of collection development in their libraries. They are the following schools: Far Eastern University, Polytechnic University of the Philippines, University of the East and University of Santo Tomas. The results are that most of the respondent libraries are already subscribing to electronic journals mainly because of their availability, accessibility and searchability and retrieval possibilities. However, print versions of the journal are not going to immediately disappear given the present economic constraints. There is a gradual increase in electronic scholarly publication. Some electronic journals are added simply as an alternative to print journals. Balance will be needed between the heavily used and the not so heavily used materials. Librarians must preserve and extend print collections while at the same time making informed choices on provision of electronic sources, especially electronic journals.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Academic libraries -- Philippines -- Metro Manila; Acquisition of serial publications; Serials control systems -- Automation